PERSEPSI MAHASISWA AKUNTANSI MENGENAI ETIKA PENYUSUNAN LAPORAN KEUANGAN: Studi Kasus Pada Mahasiswa Program Studi Akuntansi Universitas Flores - Nio, Elvisius T; Banda, Falentina L; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2021)
The purpose of this study was to determine the perception of accounting students regarding the ethics of preparing financial statements. The population in this study were all students of the Accounting Study Program. Based on the purposive sampling method, this study used a sample of 86 respondents and the sample consisted of 22 upper-level students and 64 lower-level students. The variable in this study is the Ethics of Financial Statement Preparation. The method used is descriptive quantitative. This study uses primary data, namely questionnaires. Data were analyzed using independent sample t-Test analysis which was processed through IBM SPSS Statistics ver 25. The results of this study indicate that: There are differences in perceptions regarding the ethics of preparing financial statements for upper-level students and lower-level students as seen in earnings management, misstatements, disclosure of information, cost benefits, and responsibility for preparing financial statements